The experience of gender dysphoria for pre‐pubescent children and their families: a review of the literature. Issue 3 (3rd April 2014) - Gregor, Claire; Davidson, Sarah; Hingley‐Jones, Helen
Abstract: In recent years, the experience of gender dysphoria has gained public prominence through an explosion of sensationalized interest in the popular media. However, childhood gender dysphoria remains poorly understood and both parents and children often find themselves having to educate professionals around them. This not only creates a sense of disconnect between family and professionals, but also means that social workers can often be unaware of the myriad of competing perspectives that seek to explain gender variance. This review of the literature seeks to provide interested social workers with an overview of gender dysphoria, current research in the field and theoretical paradigms, with a view to promoting understanding and better practice with families in this little understood field.